2022
DOI: 10.1111/micc.12783
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and visualization methods for detecting functional activation using laser speckle contrast imaging

Abstract: Background: Previous studies have used regional cerebral blood flow (CBF) hemodynamic response to measure brain activities. In this work, we use a laser speckle contrast imaging (LSCI) apparatus to sample the CBF activation in somatosensory cortex (S1BF) with repetitive whisker stimulation. Traditionally, the CBF activations were processed by depicting the change percentage above baseline; however, it is not clear how different methods influence the detection of activations.Aims: Thus, in this work we investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…[ 174 ] Besides, different approaches for assessment of CBF changes during activation in the somatosensory cortex by repetitive whisker stimulation have been analyzed. [ 175 ] It has been shown that principal component analysis (PCA) can significantly reduce the noise in speckle contrast data. The fast Fourier transform and general linear model analysis were performed to estimate the cortex activation.…”
Section: Recent Progress In Dls‐based Imaging Of Blood Flowmentioning
confidence: 99%
“…[ 174 ] Besides, different approaches for assessment of CBF changes during activation in the somatosensory cortex by repetitive whisker stimulation have been analyzed. [ 175 ] It has been shown that principal component analysis (PCA) can significantly reduce the noise in speckle contrast data. The fast Fourier transform and general linear model analysis were performed to estimate the cortex activation.…”
Section: Recent Progress In Dls‐based Imaging Of Blood Flowmentioning
confidence: 99%
“…Statistical analysis, including techniques like wavelet transform, and spectral analysis methods such as fast Fourier transform (FFT), enhance the interpretability of LSCI data by decomposing complex blood flow signals into simpler components [20][21][22]. This helps in identifying specific physiological phenomena or vascular responses, such as those occurring during reactive hyperemia.…”
Section: Introductionmentioning
confidence: 99%
“…Statistical analysis, including techniques like wavelet transform, and spectral analysis methods such as Fast Fourier Transform (FFT), enhance the interpretability of LSCI data by decomposing complex blood flow signals into simpler components [20][21][22]. This helps in identifying specific physiological phenomena or vascular responses, such as those occurring during reactive hyperemia.…”
mentioning
confidence: 99%